Motivation and Test Anxiety in Test Performance Across Three Testing Contexts: The CAEL, CET, and GEPT. Issue 2 (30th May 2013) - Cheng, Liying; Klinger, Don; Fox, Janna; Doe, Christine; Jin, Yan; Wu, Jessica
Abstract : This study examined test‐takers' motivation, test anxiety, and test performance across a range of social and educational contexts in three high‐stakes language tests: the Canadian Academic English Language (CAEL) Assessment in Canada, the College English Test (CET) in the People's Republic of China, and the General English Proficiency Test (GEPT) in Taiwan. The researchers issued a questionnaire exploring motivation, test anxiety, and perceptions of test importance and purpose to test‐takers in each of the three contexts. A total of 1, 281 valid questionnaire responses were obtained: 255 from CAEL, 493 from CET, and 533 from GEPT. Questionnaire responses were linked to each test‐taker's respective test performance. The results illustrate complex interrelationships of test‐takers' motivation and test anxiety in their test performance. Differences in motivation and test anxiety emerged with regard to social variables (i.e., test importance to stakeholders and test purposes). Further, motivation and test anxiety, along with personal variables (i.e., gender and age), were associated with test performance. Given that motivation and test anxiety have typically been examined separately and in relation to a single testing context, this study addresses an important research gap.